Practical guide to structuring the Methods and Results sections in clinical and epidemiological studies - Claire Gudex; Charlotte Leboeuf-Yde (Chiropractic & Manual Therapies, 2026)
Abstract This is the second of three articles that provide step-by-step guides on how to structure the content of a scientific article to ensure a coherent and relevant text. This article deals with the Methods and Results sections. We start by explaining the purpose and content of these sections and then provide a practical guide for planning the structure of each section as preparation for writing the full text later. Thus, we describe ten steps for structuring the Methods section and six steps for structuring the Results section. We illustrate our explanations with text examples selected from this journal to show how authors have approached various aspects of these two sections. After some tips for constructing informative tables and figures, we discuss the use of artificial intelligence when preparing the Methods and Results sections. The Methods section is fundamental to your reader understanding your study and trusting the validity of your findings, while the Results section provides answers to your stated research objectives or questions. Transparency and completeness are essential in both sections to assist your reader and reflect your academic integrity.